Performance of CSF Lactate for Diagnosis of Acute Bacterial Meningitis in Paediatric Population (Bangladesh Journal of Neuroscience, 2026)
Background: Meningitis is a grave condition which demands prompt diagnosis and early treatment. Proper diagnosis needs identification of the causative agent. But isolation of organism is not always possible. Previous studies found that CSF lactate is increased in bacterial meningitis and its level does not alter immediately with treatment. So, CSF lactate can be used as an important marker to diagnose acute bacterial meningitis in children.Methodology: This cross-sectional study conducted at the department of Paediatrics in Dhaka Medical College and Hospital (DMCH), Dhaka, Bangladesh from September, 2018 to February, 2020. After initial screening of 132 suspected meningitis finally, 96 patients of acute meningitis were included in the study and divided into bacterial (n=34) and viral (n=62) meningitis groups based on the CSF results. CSF lactate in these two categories was analyzed. Based on the receiver-operator characteristic (ROC) curve, area under curve was identified for CSF lactate. Best cut off value along with sensitivity and specificity was calculated.Results: Among 96 patients, almost two third (64.6%) patients were diagnosed with viral meningitis and 34 (35.4%) with bacterial meningitis. Six (17.6%) patients were found blood culture positive in bacterial meningitis group. Twenty three (67.6%) patients were found with positive CSF gram staining and ten (29.4%) patients showed positive growth in CSF culture in bacterial meningitis group. The mean CSF lactate was 5.7±1.8mmol/L in bacterial meningitis group and 1.8±0.7 mmol/L in viral meningitis group. The difference was statistically significant (p2.2 mmol/L using Youden’s Index with sensitivity 97.1%, specificity 87.1%.Conclusion: In this study CSF lactate >2.2 mmol/L was found highly sensitive and specific for diagnosis of acute bacterial meningitis in paediatric population.